The Interactions of Parasite Calreticulin With Initial Complement Components: Consequences in Immunity and Virulence - Ramírez-Toloza, Galia; Aguilar-Guzmán, Lorena; Valck, Carolina; Ferreira, Viviana P.; Ferreira, Arturo (Frontiers in Immunology, 2020)
Because of its capacity to increase a physiologic inflammatory response, to stimulate phagocytosis, to promote cell lysis and to enhance pathogen immunogenicity, the complement system is a crucial component of both the innate and adaptive immune responses. However, many infectious agents resist the activation of this system by expressing or secreting proteins with a role as Complement regulatory, mainly inhibitory, proteins. Trypanosoma cruzi, the causal agent of Chagas disease, a reemerging microbial ailment, possesses several virulence factors with capacity to inhibit complement, at different stages of activation. T. cruzi calreticulin (TcCalr), is a highly-conserved, endoplasmic reticulum-resident chaperone, that the parasite translocates to the extracellular environment, where it exerts a variety of functions. Among these functions, TcCalr binds C1, MBL and ficolins, thus inhibiting the classical and lectin pathways of complement, at their earliest stages of activation. Moreover, the TcCalr/C1 interaction also mediates infectivity by mimicking a strategy used by apoptotic cells for their removal. More recently, it has been determined that these Calr strategies are also used by a variety of other parasites. In addition, as reviewed elsewhere, TcCalr inhibits angiogenesis, promotes wound healing and reduces tumor growth. Complement C1 is also involved in some of these properties. Knowledge on the role of virulence factors such as TcCalr, and their interactions with complement components, in host–parasite interactions, may lead towards the description of new anti-parasite therapies and prophylaxis.